Penyuluhan Kesehatan Tentang Hipertensi di Gampong Cot Jambo Kecamatan Blang Bintang Kabupaten Aceh Besar - Afrianti, Novi; Yuliana, Dewi; Fitriani, Lisa (PT.Mantaya Idea Batara, 2023)
Hypertension is still the highest health problem globally with its incidence increasing every year. This disease is characterized by increased blood pressure above 140/90 mmHg, dizziness, neck stiffness, and others. Hypertension is caused by many factors such as heredity, lifestyle, age, and others. According to the initial survey, the patient's knowledge was still lacking about hypertention, this was a problem in Gampong Cot Jambo Aceh Besar, so it was important to be educate. This activity is carried out in the Meunasah gampong Cot Jambo, Blang Bintang District. The method used in carrying out this service is by way of discussion, lecture and question and answer. The result show of this service found that the patient in participating in this counseling activity was very enthusiastic, which was marked by asking questions and a commitment to control blood pressure regularly and do a hypertension diet.